Identification of key genes involved in collagen hydrogel-induced chondrogenic differentiation of mesenchymal stem cells through transcriptome analysis: the role of m6A modification - Chaotao Chen; Kai Xiong; Kanglu Li; Bo Zhou; Jianwen Cheng; Bo Zhu; Li Zheng; Jinmin Zhao (Journal of Materials Science: Materials in Medicine)
Abstract Collagen hydrogel has been shown promise as an inducer for chondrogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), contributing to the repair of cartilage defects. However, the precise molecular mechanism underlying this phenomenon remains poorly elucidated. Here, we induced chondrogenic differentiation of BMSCs using collagen hydrogel and identified 4451 differentially expressed genes (DEGs) through transcriptomic sequencing. Our analysis revealed that DEGs were enriched in the focal adhesion pathway, with a notable decrease in expression levels in the collagen hydrogel group compared to the control group. Protein-protein interaction network analysis suggested that actinin alpha 1 (ACTN1) and actinin alpha 4 (ACTN4), two proteins also involved in cytoskeletal recombination, may be crucial in collagen hydrogel-induced chondrogenic differentiation of BMSCs. Additionally, we found that N6-methyladenosine RNA methylation (m6A) modification was involved in collagen hydrogel-mediated chondrogenic differentiation, with fat mass and obesity-associated protein (FTO) implicated in regulating the expression of ACTN1 and ACTN4. These findings suggest that collagen hydrogel might regulate focal adhesion and actin cytoskeletal signaling pathways through down-regulation of ACTN1 and ACTN4 mRNA via FTO-mediated m6A modification, ultimately driving chondrogenic differentiation of BMSCs. In conclusion, our study provides valuable insights into the molecular mechanisms of collagen hydrogel-induced chondrogenic differentiation of BMSCs, which may aid in developing more effective strategies for cartilage regeneration. Graphical Abstract